The pastoral epistles in the new English Bible, with introduction and commentary - Barrett, Charles Kingsley (Oxford, UK Oxford UP, 1963)
Includes bibliographical references and indes.
Keywords: Bible. N.T. Pastoral epistles -- commentaries